2021
DOI: 10.1093/chemse/bjab024
|View full text |Cite
|
Sign up to set email alerts
|

Central Nervous System Processing of Floral Odor and Mother’s Milk Odor in Infants

Abstract: Newborns have a functioning sense of smell at birth, which appears to be highly significant for feeding and bonding. Still, little is known about the cerebral odor processing in this age group. Studies of olfactory function relied mostly on behavioral, autonomic and facial responses of infants. Aim The aim of the present study was to investigate central odor processing in infants focusing on EEG-derived responses to biologically significant od… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
0
6
2
Order By: Relevance
“…However, in 2001 a research group demonstrated, using near-infrared spectroscopy, that a change in blood oxygenation of premature infants could be detected in the orbitofrontal cortex after olfactory stimulation with disinfectant and detergent [3]. Electroencephalogram (EEG) techniques have broadly been used to measure central odor processing in adults and children [4][5][6]. EEG has a high temporal resolution and is more stable to movement artifacts compared to magnetic resonance imaging (MRI).…”
Section: Department Of Pediatric Neurology Charité -Universitätsmediz...mentioning
confidence: 99%
See 4 more Smart Citations
“…However, in 2001 a research group demonstrated, using near-infrared spectroscopy, that a change in blood oxygenation of premature infants could be detected in the orbitofrontal cortex after olfactory stimulation with disinfectant and detergent [3]. Electroencephalogram (EEG) techniques have broadly been used to measure central odor processing in adults and children [4][5][6]. EEG has a high temporal resolution and is more stable to movement artifacts compared to magnetic resonance imaging (MRI).…”
Section: Department Of Pediatric Neurology Charité -Universitätsmediz...mentioning
confidence: 99%
“…From the age of 28–29 weeks of gestation, a change in EEG to external stimuli can be observed [ 7 ]. The aim of the present study was to investigate the possibility of detecting central odor processing in premature infants by analyzing olfactory-induced EEG changes using Fast Fourier transformation (FFT) as an already established method in older term-born infants [ 6 ]. The previous study from our group demonstrated that EEG method and FFT analysis were feasible for mature infants and showed that EEG amplitudes in the δ frequency band differed significantly after the presentation of breast milk in comparison to an odorless control stimulus and farnesol odor, especially in frontal recording positions [ 6 ].…”
mentioning
confidence: 99%
See 3 more Smart Citations